2021
DOI: 10.3174/ajnr.a7196
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Stent-Assisted Coiling of Unruptured Intracranial Aneurysms Using Low-Profile Stents in Small Parent Arteries

Abstract: BACKGROUND AND PURPOSE: Stent-assisted coiling of intracranial aneurysms arising from small vessels (# 2.0 mm) is a common procedure. However, data regarding its treatment outcomes are scarce. This study evaluated the clinical and radiologic outcomes of stent-assisted coiling using low-profile stents for aneurysms of small parent arteries. MATERIALS AND METHODS:From November 2015 to October 2020, sixty-four patients with 66 aneurysms arising from parent arteries of #2.0 mm were treated with stent-assisted coil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
1
1
Order By: Relevance
“…In our study, a total of 130 aneurysms (96.3%) had a similar obliteration results, and the complete embolization rate (Raymond class I) reached 82.2%, which is within the range reported in the relevant literature ( 6 8 , 21 ). Immediate postoperative angiography in the study by Kim et al ( 13 ) showed 57.6% of aneurysms rated as Raymond class I, 19.7% as Raymond class II, and 22.7% as Raymond class III. At the 6-month interim follow-up results, they found a complete embolization rate of 87.9%.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…In our study, a total of 130 aneurysms (96.3%) had a similar obliteration results, and the complete embolization rate (Raymond class I) reached 82.2%, which is within the range reported in the relevant literature ( 6 8 , 21 ). Immediate postoperative angiography in the study by Kim et al ( 13 ) showed 57.6% of aneurysms rated as Raymond class I, 19.7% as Raymond class II, and 22.7% as Raymond class III. At the 6-month interim follow-up results, they found a complete embolization rate of 87.9%.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, low-profile stents have a greater advantage in terms of microcatheter diameter, especially for aneurysms located at small size vessels. Kim et al ( 13 ) achieved a 100% technical success rate with the placement of low-profile stents (LVIS Jr or Neuroform Atlas) in 66 aneurysm-carrying arteries (<2.0 mm). Earlier, Santillan et al ( 19 ) successfully delivered all LVIS Jr. stents in 35 aneurysms with an I.D.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stent-assisted coiling (SAC) is a popular treatment option for both small and complex intracranial aneurysms, as it facilitates coil packing of wide-necked aneurysms that are at risk of coil dislocation and herniation into the parent target vessel, causing potentially periprocedural or delayed ischemic complications [ 1 , 2 ]. Furthermore, SAC allows higher densities of endo-saccular coil embolization and, as a result, higher occlusion and lower recurrence rates due to improved aneurysm thrombosis in comparison to coiling alone, which is not suitable in the majority of wide-necked aneurysm [ 3 ].…”
Section: Introductionmentioning
confidence: 99%